Defensoria Pública do Estado de São Paulo: promoção da cidadania e governança democrática - Reinert, Lúcia Thomé (2016)
The Public Defense is the institution constitutionally provided to exercise legal assistance, full and free for the unfortunate and vulnerable population of the Democratic State of Law. It is known that the Republic Constitution of 1988, founded on the principles of Dignity of the Human Being and Citizenship, reinforce the importance of popular participation in building a Democratic State of Law. Consequently, is imperative to ensure to all the necessary Citizenship needed to implement the access to justice. It results in the importance of the Public Defense as a constitutional entity projected to serve as an instrument of citizenship, as well as to assure everyone the effective participation in the justice system. As a consequence, with the aim of ensuring the creation of an inclusive justice system, plural and egalitarian, the Public Defense, and especially the Public Defense of the State of São Paulo, provides tools to facilitate the access of vulnerable people to the justice system, once its recognizes the social participation as the basis of a Democratic State of Law. It is necessary to study the legal field that governs the feasibility of operation of the Public Defense, either at the national level, and internationally, as well as study and analyze research carried out in the country which recognizes the important role of the Public Defense for the realization of the social participation and implementation of citizenship. Besides, it s quite important to analyze the III Diagnostic of Public Defenses in Brazil, as well as decisions of the Supreme Court that recognizes the role of the Public Defense as an essential link to provide access of the socially excluded to Law and Justice by contributing to the establishment of a democratic governance within the justice system